Isolation and Antibacterial Properties of Phenyl Acrylic Acid Derivatives from Balanophora elongata Blume - Nanda Putra; Goldha Faroliu; Nova Syafni; Nofrizal; Amri Bakhtiar; Dayar Arbain (Institute for Research and Community Services (LPPM) ITB, 2021)
Balanophora elongata (Balanophoraceae) is a tropical parasitic flowering plant 9 cm in height. Four known phenyl acrylic acid derivatives, methyl caffeate (1), caffeic acid (2), 1,6-di-O-caffeoyl-β-D-glucopyranose (3), and coniferin (4), were isolated from this plant. Structural elucidation of the isolated compounds was determined by IR, LC-ESI-MS, 1D and 2D NMR. Extracts and isolated compounds were tested toward some standard human pathogenic bacteria using the agar disk diffusion method. Their inhibition zones were compared to that of chloramphenicol as positive control. Compound 1 showed inhibition toward Streptococcus mutans, while compound 3 and 4 inhibited Staphylococcus aureus.